Distribution and Differentiation Patterns of Sympatric Squids Alloteuthis media and Alloteuthis subulata (Cephalopoda: Loliginidae) Using Morphological and Molecular Approaches - Alujević, Karla; Šegvić-Bubić, Tanja; Isajlović, Igor; Trumbić, Željka; Petrić, Mirela (Frontiers in Marine Science, 2022)
Identification of the two sympatric species, Alloteuthis media and Alloteuthis subulata, has long relied on a set of identifying morphometric parameters and descriptive guidelines. To resolve taxonomic status of Alloteuthis in the Eastern Adriatic, we used morphological and molecular approach on a dataset collected during MEDITS expeditions sampling the entire Eastern Adriatic over consecutive summers. Phylogenetic analyses inferred from mitochondrial DNA cytochrome oxidase I (COI) gene sequences confirmed presence of both species in the Eastern Adriatic, with A. subulata occurring only in its central and southern parts. Analyses of genetic diversity showed that A. subulata samples in the Eastern Adriatic shared a single haplotype while A. media showed high haplotype diversity. Comparison of Eastern Adriatic A. media samples and populations from other regions showed statistically significant genetic differentiation between the Atlantic haplotypes and each of the Adriatic, Aegean, and Ionian populations. Conversely, A. subulata had low genetic diversity with only two haplotypes present across samples collected globally. There was no single morphometric character with strong enough power to discriminate between species, however, when morphological traits were looked as a composite metric rather than in isolation, the majority of individuals were correctly classified into one of three groups (A. media males or females and A. subulata).